Prevalence of Toxocara and Toxascaris infection among human and animals in Iran with meta-analysis approach - Eslahi, Aida Vafae; Badri, Milad; Khorshidi, Ali; Majidiani, Hamidreza; Hooshmand, Elham; Hosseini, Hamid; Taghipour, Ali; Foroutan, Masoud; Pestehchian, Nader; Firoozeh, Farzaneh; Riahi, Seyed Mohammad; Zibaei, Mohammad (BMC infectious diseases, 2020)
Toxocariasis is a worldwide zoonotic parasitic disease caused by species of Toxocara and Toxascaris, common in dogs and cats. Herein, a meta-analysis was contrived to assess the prevalence of Toxocara/Toxascaris in carnivore and human hosts in different regions of Iran from April 1969 to June 2019. The available online articles of English (PubMed, Science Direct, Scopus, and Ovid) and Persian (SID, Iran Medex, Magiran, and Iran Doc) databases and also the articles that presented in held parasitology congresses of Iran were involved. The weighted prevalence of Toxocara/Toxascaris in dogs (Canis familiaris) and cats (Felis catus) was 24.2% (95% CI: 18.0-31.0%) and 32.6% (95% CI: 22.6-43.4%), respectively. Also, pooled prevalence in jackal (Canis aureus) and red fox (Vulpes vulpes) was 23.3% (95% CI: 7.7-43.2%) and 69.4% (95% CI: 60.3-77.8%), correspondingly. Weighted mean prevalence of human cases with overall 28 records was 9.3% (95% CI: 6.3-13.1%). The weighted prevalence of Toxocara canis, Toxocara cati, and Toxascaris leonina was represented as 13.8% (95% CI: 9.8-18.3%), 28.5% (95% CI: 20-37.7%) and 14.3% (95% CI: 8.1-22.0%), respectively. Our meta-analysis results illustrate a considerable prevalence rate of Toxocara/Toxascaris, particularly in cats and dogs of northern parts of Iran. The presence of suitable animal hosts, optimum climate and close contact of humans and animals would have been the reason for higher seroprevalence rates of human cases in our region. Given the significance clinical outcomes of human Toxocara/Toxascaris, necessary measures should be taken.